ISDN explained worldwide network and applications technology - Griffiths, John M (John Wiley & Sons, 1992)
This text goes into the principles of all facets of the ISDN operation, giving an overview to set the operations in context and to act as an introduction to detailed standards, recommendations and specifications. The author looks at short and long term applications of ISDN that have become apparent since the first edition in 1990. New terminal equipment has emerged and this is described in chapter 8. Other additions include a more detailed consideration of supplementary services and an update on the situation on inter-PABX signalling and Broadband ISDN. An annex explaining the use of SDL in specifying ISDN interfaces is provided.